2021
DOI: 10.3390/jcm10051064
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection: Modulator of Pulmonary Embolism Paradigm

Abstract: Pulmonary embolism (PE) is a life-threatening complication arising from venous thromboembolism with a difficult diagnosis and treatment and is often associated with increased mortality and morbidity. PE had a significantly low incidence prior to the COVID-19 epidemic. This condition saw a sharp surge during the COVID-19 pandemic, indicating an evident viral influence on PE’s pathophysiology in COVID-19 patients. The hypercoagulable state induced by the viral load seems to be the major contributor, and the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 121 publications
0
14
0
1
Order By: Relevance
“…The risk factors of thromboembolism or PE in COVID-19 patients are not the same as traditional PE risk factors. Traditional risk factors including lower limb fractures, heart failure, hip or knee replacement surgeries, myocardial infarction, spinal trauma, post-partum period do not seem to increase the risk in COVID-19 patients, but sure there will be some relevance of these conditions on the occurrence of PE [7]. African American race and obesity are found to increase the risk of PE in COVID-19 patients.…”
Section: Risk Factorsmentioning
confidence: 91%
See 4 more Smart Citations
“…The risk factors of thromboembolism or PE in COVID-19 patients are not the same as traditional PE risk factors. Traditional risk factors including lower limb fractures, heart failure, hip or knee replacement surgeries, myocardial infarction, spinal trauma, post-partum period do not seem to increase the risk in COVID-19 patients, but sure there will be some relevance of these conditions on the occurrence of PE [7]. African American race and obesity are found to increase the risk of PE in COVID-19 patients.…”
Section: Risk Factorsmentioning
confidence: 91%
“…African American race and obesity are found to increase the risk of PE in COVID-19 patients. There is no strong relationship between cardiovascular comorbidities and the risk of pulmonary embolism in COVID-19 patients [7]. Various studies reported that the clinical and biological parameters in COVID-19 patients driven by inflammation and coagulopathy increase the risk of PE.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations